The Impact of Hydropower Energy on the Environmental Kuznets Curve in Malaysia - Sinaga, Obsatar; Alaeddin, Omar; Jabarullah, Noor H. (International Journal of Energy Economics and Policy, 2018)
The present research examines the effect of hydropower energy consumption in testing the Environmental Kuznets Curve in Malaysia by using the annual time series data over the period from 1978 to 2016. The present research applied the advance econometrics to serve the purpose of investigation and therefore used the Auto Regressive Distributed Lag (ARDL) bound testing approach for assessing the presence of long-run relationship between the variables. The results of ARDL bound testing approach confirm the valid long run relationship between hydropower energy consumption and economic growth with carbon dioxide emission in Malaysia. The final outcomes confirm that hydropower energy consumption and square of economic growth have significant and negative impact on carbon dioxide emission whereas, the economic growth have a significant and positive impact on carbon dioxide emission. Furthermore, results also confirm the existence of inverted U-Shape curve in Malaysia. The results provide a solid evidence for the policymakers to focus on hydropower energy consumption while formulating the policy for the reduction of environmental degradation in Malaysia. Keywords: Hydropower, green energy, renewable energy, sustainable development. JEL Classifications: O11, Q20, Q23 DOI: https://doi.org/10.32479/ijeep.7328